Eksistensi dan Prospek Pengaturan Perppu Dalam Sistem Norma Hukum Negara Republik Indonesia - Febriansyah, Reza Fikri (Jurnal Legislasi Indonesia, 2009)
The government regulation in lieu of law (also known as Perppu) is a kindof legislation which reflecting a presidential power to solve an emergency.It should consider on Pancasila and the Indonesian Constitution Year of1945 as the Basic Law (Staatsfundamentalnorm) and being a considerationfor the kind of legislation below. There are some legal problems concerningthe existence and the function of The Government Regulation in lieu of Law.So, the reforming process of the Law Number 10 Year of 2004 concerningThe Making of Legislation should accommodate a progressive ideas in frameof the existence and the function of The Government Regulation in lieu ofLaw, particularly, to search the solution of how to define “a state ofemergency”.